2012
DOI: 10.1177/1947601912455322
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of MDM2 Binding Partners

Abstract: Mdm2 is an essential regulator of the p53 tumor suppressor. Mdm2 is modified at transcriptional, post-transcriptional, and post-translational levels to control p53 activity in normal versus stressed cells. Importantly, errors in these regulatory mechanisms can result in aberrant Mdm2 expression and failure to initiate programmed cell death in response to DNA damage. Such errors can have severe consequences as evidenced by tumor phenotypes resulting from amplification at the Mdm2 locus and changes in post-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 163 publications
(174 reference statements)
2
56
0
1
Order By: Relevance
“…This observation indicates that Mdm2 gene amplification indeed results in its overexpression, but other mechanisms may also confer Mdm2 upregulation. Extensive studies have indicated that upregulation of Mdm2 results from elevated transcription, increased mRNA stability, enhanced translation and altered post-translational modification (reviewed in 22, 47). In addition, these mechanisms are associated with upregulation of Mdm2 in tumors.…”
Section: Elevated Levels Of Mdm Proteins In Human Tumorsmentioning
confidence: 99%
“…This observation indicates that Mdm2 gene amplification indeed results in its overexpression, but other mechanisms may also confer Mdm2 upregulation. Extensive studies have indicated that upregulation of Mdm2 results from elevated transcription, increased mRNA stability, enhanced translation and altered post-translational modification (reviewed in 22, 47). In addition, these mechanisms are associated with upregulation of Mdm2 in tumors.…”
Section: Elevated Levels Of Mdm Proteins In Human Tumorsmentioning
confidence: 99%
“…11 However, Mdm2 has also been shown to influence tumor phenotypes though p53-independent mechanisms. 12 For example, in CRC, several studies link the Mdm2 SNP309-G allele to exacerbated tumor phenotypes and increased overall risk, specifically in pre-menopausal women. 8,9 Importantly, this Mdm2 SNP309-G -associated risk is lost in women once they are post-menopausal.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Numerous binding partners of Mdm2 and/or p53 influence their functional interaction and p53 activity. 1,21 One important example is the alternative reading frame (ARF) tumor suppressor encoded by the INK4a/ARF locus. 22 Oncogene activation and sustained DNA damage induce expression of ARF, which binds to Mdm2, inhibits its E3 ubiquitin ligase activity and restricts the p53 tumor suppressor is controlled by an interactive network of factors that stimulate or inhibit its transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%